Hadits Tentang Evaluasi Pendidikan dan Karakteristiknya - Levi Fitriani; Ayu Lika Rahmadani; M. Aufar Saputra Pratama Erawan (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2021)
Educational evaluation is very essential to determine the success obtained by students, An educational evaluation also serves to see whether the programs that have been implemented have useful improvements to make the program more effective. In addition, the assessment is to decide the degree of progress of the program in training. During the time spent in Islamic training, the best approach to discover how fruitful the learning targets or member’s ability is by assessing. The strategy utilized in this investigation is the examination of writing content identified with the hadith about instructive assessment. The consequences of this investigation show that instructive assessment is a cycle to decide the benefit of something identified with Islamic training, the strategy for understanding the study of hadith (fiqh al-hadith) is a measurement that is no less significant after dirayah science and musthalah hadith. This is on the grounds that fiqh al-hadits is an investigation that attempts to profoundly investigate and comprehend the messages contained in the Prophet's hadith to be drilled.